Faktor-Faktor yang Mempengaruhi Aktivitas Hedging dengan Instrumen Derivatif Valuta Asing - Guniarti, Fay (JDM (Jurnal Dinamika Manajemen), 2014)
The objective of the study was to know the factors which influence the hedging activity with foreign currency derivative instruments at non-financial companies listed on the Indonesia Stock Exchange in 2010-2012. The data of the research were secondary data which was downloaded from the Indonesia Stock Exchange website. The population of the study was all companies listed in Indonesia Stock Exchange in the period of 2010-2012. There were 77 companies which had the transaction exposure andcomplete data for analysis. From those samples, only 28 companies did hedging activities during the period of observation and 49 companies did not do hedging activities.The data were analyzed by Logistic Regression Analysis to test the hypothesis. The test result showed that analysis model gave the accuracy 79.2% and the research variables; leverage, liquidity, firm size, and financial distress significantly influenced the probability prediction of hedging activity with 5% level of significancy, while the research variables; firm value and growth opportunity did not give significant influence.